Calpain system protein expression in carcinomas of the pancreas, bile duct and ampulla - Storr, Sarah J.; Zaitoun, Abed M.; Arora, Arvind; Durrant, Lindy G.; Lobo, Dileep N.; Madhusudan, Srinivasan; Martin, Stewart G. (BioMed Central, 2012)
Background: Pancreatic cancer, including cancer of the ampulla of Vater and bile duct, is very aggressive and has a poor five year survival rate; improved methods of patient stratification are required. Methods: We assessed the expression of calpain-1, calpain-2 and calpastatin in two patient cohorts using immunohistochemistry on tissue microarrays. The first cohort was composed of 68 pancreatic adenocarcinomas and the second cohort was composed of 120 cancers of the bile duct and ampulla. Results: In bile duct and ampullary carcinomas an association was observed between cytoplasmic calpastatin expression and patient age (P = 0.036), and between nuclear calpastatin expression and increased tumour stage (P = 0.026) and the presence of vascular invasion (P = 0.043). In pancreatic cancer, high calpain-2 expression was significantly associated with improved overall survival (P = 0.036), which remained significant in multivariate Cox-regression analysis (hazard ratio = 0.342; 95% confidence interva l = 0.157-0.741; P = 0.007). In cancers of the bile duct and ampulla, low cytoplasmic expression of calpastatin was significantly associated with poor overall survival (P = 0.012), which remained significant in multivariate Cox-regression analysis (hazard ratio = 0.595; 95% confidence interval = 0.365-0.968; P = 0.037). Conclusion: The results suggest that calpain-2 and calpastatin expression is important in pancreatic cancers, influencing disease progression. The findings of this study warrant a larger follow-up study. Keywords: Calpain, Calpastatin, Pancreas, Ampulla, Bile duct, Cancer